Less is more: Biased loss of CpG dinucleotides strengthens antiviral immunity - Sauter, Daniel; Kirchhoff, Frank (PLOS Biology, 2021)
Viruses may not only affect our daily lives but also shape our genome evolution. A recent study shows that the zinc-finger antiviral protein (ZAP) drives CpG suppression in a biased manner. Genes involved in the defense against viral invaders are particularly CpG suppressed to avoid self-targeting and to promote an effective immune response.